(3GdPcGA GdhLOGfi hGdMH Hjf GdRhLjf cefHFjf HGdQVG GdRhGLi (B/ s - (3fUQI efUhQ YHOGdeLjO YHOGdYGds; (3GSGeI GHhSQjY (B: s; (3aGOjI YdhGf (B: s ((3GdbGgQI (B: s (3fUQI efUhQ YHOGdeLjO YHOGdYGd (B: s, 2012)
(3JgOa GdOQGSI GdMGdjI Gdi GdcTa Yf OhQ GdPcGA GdhLOGfi h JchfJ GdYjfI ef (B200 (3RhL h RhLGJge (B(100(3RhL (B: 100 (3RhLI(B) (3JJQGhM CYeGQge Hjf (B(25 - 40 )(3SfI h WHb Ydi CaQGO GdYjfI ebjGS GdPcGA GdhLOGfi cbOQI dOi GdCRhGL h GdRhLGJ h Pdc EYOGO GdHGMKI h ebjGS eKdK GdMH dSJjQfHQL (B1997 (3h ebjGS GdQVG GdRhGLi dahQS h CdSf cTaJ fJGFL GdOQGSI HhLI YGe Yf GMJdGd GdMH GdOhQ GdJfHDi GdGhd HGdQVG GdRhGLi HGdfSHI Gdi aQhV GdOQGSI GdGQHYI ceG JHjf Gf GdPcGA GdhLOGfi hGdMH dOi GdGRhGL jSgeGf ai GdJfHD HQVGge GdRhGLi hYdi GdQZe ef Gf GdMH dOi GdGRhGL jSge ai GdJfHD HQVG RhLGJge jNJai OhQ GdPcGA GdhLOGfi dOjge ai GdJfHD HQVG RhLGJge cPdc GJVM GSgGe GdMH dOi GdRhLGJ ai GdJfHD HQVGgf GdRhGLi Ydi Mjf GNJaJ GdbOQI ddPcGA GdhLOGfi dOjgf ai GdJfH HQVGgf GdRhGLis
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdBOGH (B- (3bSe Yde GdfaSs
(3UOQ GjVG cbQU eOeLs
Keywords: (3GdMH Hjf GdRhLjf s; (3GdPcGA GdhLOGfi s; (3GdQVG GdRhGLi s